Cover Image. (1st September 2019) - Zhu, Rusong; Wang, Hai; Yin, Guofu; Ding, Zhengtao
Abstract : The cover image is based on the Research Article High performance nonlinear adaptive control of temperature in cryogenic wind tunnel by Rusong Zhu et al., https://doi.org/10.1002/rnc.4669 .